P87 Peripheral markers of immune activation are not associated with depression and cognitive impairment before and during antiviral therapy in chronic hepatitis C infection. (16th November 2010) - Gess, M; Forton, D
Abstract : Introduction: Cognitive impairment (CI) and depression are associated with chronic HCV infection and its treatment with alpha-interferon (IFN). Chronic immune activation may predispose susceptible individuals to IFN-induced CNS effects. Neopterin (Neo) and beta-2-microglobulin (ß2m) are both IFN-induced markers of cellular immune activation. Raised serum Neo concentrations have been linked with CI in a number of inflammatory states. Aim: We hypothesised that peripheral markers of immune activation might identify/predict patients who develop CNS effects on IFN. Method: 42 HCV-infected patients (RNA+ve, HIV−ve) with mild liver disease and no significant comorbidities were compared to 20 matched controls. Subjects completed depression questionnaires (HADS-D) and cognitive testing on a computerised battery (United BioSource, UK) after appropriate training, at baseline, week 4 (W4) and W12. Serum Neo was measured by ELISA, ß2m nephelometrically. Results: At baseline 28% of patients showed significant deficits in tests of attention, 12% had depressive symptoms (HADS-D>8). Neo and ß2m levels were significantly greater in HCV patients compared to controls (mean 8.3 SD (2.1) vs 6.6 (2.6) and 2.4 (0.4) vs 1.7 (0.6), p<0.002) but this was not associated with depression or CI. On treatment, Neo and ß2m levels increased significantly at W4 (mean change (Δ) 5.3 and 0.8 respectively, p<0.001). ß2m increased further at W12. Neo and ß2m correlated closely at all time points (p<0.001). Rates of significant depressive symptoms increased on treatment to 43% by W12 (p=0.003). Baseline values and Δ Neo and Δ ß2m did not predict incidence of depression. Mean HADS-D scores increased from 3.5 (3.5) at baseline to 7.1 (5.1) at W12 (p<0.001). Δ HADS-D was not associated with Δ Neo or Δ ß2m. Performance in the attention test deteriorated from 1166 (127) ms at baseline to 1216 (148) ms at W12 (p=0.001). 33% of patients had impairments >1SD compared to baseline performance, which were not associated with Δ HADS-D, Δ Neo or Δ ß2m. Neither baseline performance nor baseline Neo or ß2m were predictive of significant on-treatment CI. There were improvements in "speed of memory" on treatment from 3452 (641) ms at baseline to 3330 (630) ms at W12 (p=0.006) which had no statistical associations. Conclusion: We confirm the high incidence of IFN- induced depression and CI. The improvements in memory are unexplained but may be due to a learning effect on the battery. The lack of an association with Neo and ß2m suggests that CNS effects of IFN are unrelated to peripheral immune activation. Emerging evidence of HCV infection of the brain and microglial activation may represent a central susceptibility to IFN-induced CNS symptoms.